2002
DOI: 10.1128/aem.68.3.1280-1289.2002
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Flagellar Rotation Is Important in Initial Attachment of Escherichia coli to Glass in a Dynamic System with High- and Low-Ionic-Strength Buffers

Abstract: The attachment rates of wild-type, smooth-swimming, tumbly, and paralyzed Escherichia coli to glass was measured at fluid velocities of 0.0044 and 0.044 cms ؊1 (corresponding to shear rates of 0.34 and 3.4 s ؊1 , respectively), in 0.02 and 0.2 M buffer solutions. At the highest ionic strength, we did not observe a significant difference in the attachment rate of wild-type and paralyzed cells at either fluid velocity. However, when the ionic strength was reduced, paralyzed bacteria attached at rates 4 and 10 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 39 publications
5
83
0
1
Order By: Relevance
“…At this point, we can only speculate as to the role (if any) of changing flagellar reversal rates in these two surface behaviors. It has been suggested that in E. coli the modulation of flagellar reversals is indeed important in surface attachment (30), although the precise role of reversals is not yet understood. In an examination of motility in semisolid agar, Wolfe and Berg found a general trend that a greater reversal frequency correlated with an overall greater swarm rate.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, we can only speculate as to the role (if any) of changing flagellar reversal rates in these two surface behaviors. It has been suggested that in E. coli the modulation of flagellar reversals is indeed important in surface attachment (30), although the precise role of reversals is not yet understood. In an examination of motility in semisolid agar, Wolfe and Berg found a general trend that a greater reversal frequency correlated with an overall greater swarm rate.…”
Section: Discussionmentioning
confidence: 99%
“…Motility may also play a role in biofilm expansion (32). The direction of flagellum rotation can affect attachment and detachment of E. coli cells (19). It has been hypothesized that counterclockwise rotation may play an important role in cell detachment and that a clockwise rotation may play a role in anchoring cells to a surface.…”
Section: Discussionmentioning
confidence: 99%
“…A Pseudomonas strain was observed by Fletcher to attach to hydrophilic surfaces via flagella, while assuming random orientations on hydrophobic surfaces (20). McClaine and Ford have found that flagellar rotation increases attachment rates of Escherichia coli bacteria to glass (30,31), although it could not be ascertained whether the bacteria were adhering by their cell bodies or by their flagella. Other researchers have observed polar (ori-ented) adhesion due to specific mechanisms (5), such as adhesin-mediated adherence to fibronectin (10), lectin-mediated adherence to Sepharose beads covalently derivatized with lactose (26), or pilus adherence to tracheal cells (54).…”
mentioning
confidence: 99%